(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Diplomacy and diplomatic relations, which are an important means of conducting political relations between states, despite being subject to strictly conservative rules, are also influenced by the development of technology. Just as the invention of the telegraph triggered its widespread application in diplomatic correspondence, the development of digital technologies contributes to the improvement of channels and the reliability of communication, so the appearance of artificial intelligence will have an impact on diplomacy and diplomatic relations in general. The report analyses the regulatory framework, explores artificial intelligence platforms with opportunities for application in diplomatic activities and concludes with some conclusions about the risks and negative consequences of its use.